Agen Depigmentasi Topikal pada Melasma: Mekanisme Kerja, Efektivitas, dan Keamanan - Ridha Aulia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Melasma is a chronic acquired hyperpigmentation disorder affecting sun-exposed facial areas and associated with ultraviolet exposure, hormonal influences, and genetic predisposition. This review aims to describe the mechanisms of action, effectiveness, and safety of topical depigmenting agents in melasma management. Hydroquinone remains the traditional gold standard through tyrosinase inhibition, while triple-combination therapy with retinoids and corticosteroids demonstrates superior reduction in Melasma Area Severity Index scores compared with monotherapy. Non-hydroquinone agents such as tranexamic acid, azelaic acid, niacinamide, cysteamine, and thiamidol show comparable efficacy with improved tolerability. Common adverse effects include erythema and irritation, with rare ochronosis linked to prolonged hydroquinone use. In conclusion, individualized multimodal strategies with strict photoprotection are essential for effective and sustained melasma control.